RNase L is a negative regulator of cell migration - Banerjee, Shuvojit (Oncotarget, 2015)
RNase L is a regulated endoribonuclease that functions in the interferon antiviral response. Activation of RNase L by 2′, 5′-oligoadenylates has been linked to apoptosis, autophagy and inflammation. Genetic studies have also suggested the possible involvement of the RNase L gene (RNASEL) on chromosome 1q25.3 in several types of cancer. Here we report that ablation of RNase L in human prostate cancer PC3 cells by CRISPR/Cas9 gene editing technology enhanced cell migration as determined both by transwell assays and scratch wound healing assays. In addition, RNase L knockdown by means of RNAi increased migration of PC3 and DU145 cells in response to either fibronectin or serum stimulation, as did homozygous disruption of the RNase L gene in mouse embryonic fibroblasts. Serum or fibronectin stimulation of focal adhesion kinase (FAK) autophosphorylation on tyrosine-397 was increased by either knockdown or ablation of RNase L. In contrast, a missense mutant RNase L (R667A) lacking catalytic activity failed to suppress cell migration in PC3 cells. However, a nuclease-inactive mutant mouse RNase L (W630A) was able to partially inhibit migration of mouse fibroblasts. Consistent with a role for the catalytic activity of RNase L, transfection of PC3 cells with the RNase L activator, 2′, 5′-oligoadenylate, suppressed cell migration. RNase L knockdown in PC3 cells enhanced tumor growth and metastasis following implantation in the mouse prostate. Our results suggest that naturally occurring mutations in the RNase L gene might promote enhanced cell migration and metastasis.